Comodo & Co / Beinah Karim … [et al.] - KARIM, BEINAH; BAHARUM, NURUL SHAHIDA; MOHD ISMAIL, ROS LAILI; YAHYA, SITI KATIJAH (2018)
Comodo & Co is a business that produces an improved glucose meter called EZ Glucose Reader. It is enhanced by technology and systems to consume less time while consumers are using it since most of diabetic patients are active people whom have less time for themselves. This device can also be used by hearing and sight disabled people because it has been changed in ways like audible system and braille. The Board of Directors of COMODO & CO are Siti Katijah as General Manager and also Operational Manager, Nurul Shahida as Marketing Manager, Beinah as Administrative Manager, and Ros Laili as Financial Manager. The idea of BZ-GlucoseReader was originally made by one of the managers and the others had agreed and all four had properly discussed this project. There are a lot of advantages as well as the advantages but to better the lives of our society, the team had ensured to overcome it one by one. While in the research and development process, the managers had hired expert help and professional advisors to successfully make this project into reality. The company's managers had contributed an equal contribution to the company and also made a loan to properly fund this process. The experts had selected the best material of thermoplastic resin and polycarbonate that mainly structures the device. Our small quality group had also managed to initiate a survey and test marketing to further claim feedbacks from society and at the same time improve the things the managers lack.